2008
DOI: 10.1007/s11999-008-0404-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher Early Mortality with Simultaneous Rather than Staged Bilateral TKAs: Results From the Swedish Knee Arthroplasty Register

Abstract: Patients with knee osteoarthritis (OA) often present with symptoms that warrant bilateral TKAs. There are potential benefits to operating on both knees on the same day, but the safety of simultaneous bilateral TKAs has been questioned. To evaluate whether there were any differences in 30-day mortality between patients having simultaneous bilateral TKAs and those having staged bilateral TKAs, we analyzed data from the Swedish Knee Arthroplasty Register and the Swedish Cause of Death Register. We included 48,931… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 18 publications
5
72
2
Order By: Relevance
“…The risk for major morbidity or mortality was comparable among the cohorts after adjustment for significant patient-related factors, which is similar to other studies using large databases finding no significant differences between same-day and staged bilateral TKAs regarding in-hospital [18] and 90-day mortality [28]. However, two meta-analyses [7,22] and the Swedish Knee Arthroplasty Register [26] showed a higher rate of mortality in same-day compared to staged bilateral TKAs. Another study [21] identified same-day bilateral TKA as a significant risk factor for perioperative mortality and concluded that same-day bilateral TKAs should be avoided in sick or elderly patients and that the medical condition of patients who have a history of cardiac or pulmonary problems should be optimized preoperatively [21].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The risk for major morbidity or mortality was comparable among the cohorts after adjustment for significant patient-related factors, which is similar to other studies using large databases finding no significant differences between same-day and staged bilateral TKAs regarding in-hospital [18] and 90-day mortality [28]. However, two meta-analyses [7,22] and the Swedish Knee Arthroplasty Register [26] showed a higher rate of mortality in same-day compared to staged bilateral TKAs. Another study [21] identified same-day bilateral TKA as a significant risk factor for perioperative mortality and concluded that same-day bilateral TKAs should be avoided in sick or elderly patients and that the medical condition of patients who have a history of cardiac or pulmonary problems should be optimized preoperatively [21].…”
Section: Discussionsupporting
confidence: 86%
“…However, despite potential advantages of the same-day approach, including exposure to the risks of anesthetic only once, one postoperative course of pain, reduced rehabilitation, and an earlier return to baseline function [10,11,23], the safety of same-day procedures has been questioned because of higher morbidity and mortality when compared with unilateral TKAs [15,22]. Several studies have attempted to compare the incidence of complications after same-day bilateral TKAs, staged bilateral TKAs, and unilateral TKAs using single institution databases, large administrative datasets, or meta-analyses [1,6,7,9,14,15,18,22,[26][27][28]. However, there are no randomized trials comparing the safety of these surgical strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advocates of simultaneous TKA have cited benefits of a single anesthetic, shorter cumulative hospital stays, patient convenience and satisfaction, and increased cost effectiveness for the healthcare system without increasing perioperative morbidity and mortality and without compromising the clinical outcomes of the operation [8, 9, 11, 12, 17, 18, 24, 27-30, 32, 35]. Opponents of the simultaneous approach cite increased perioperative complications, including pulmonary embolism, major cardiac events, ileus, higher transfusion rates, confusion, and death [1,4,12,15,21,23,27,33,35]. Concern also exists regarding the financial disincentive to the surgeon for performing bilateral simultaneous arthroplasty procedures [2,6,28].…”
Section: Introductionmentioning
confidence: 99%
“…But these benefits may come at a serious cost to patient safety, as welldesigned studies have identified greater likelihoods of serious complications occurring in patients having same-day, bilateral surgeries compared to those having staged, bilateral surgeries [4,5].…”
Section: T Has Been Nearly 40 Years Sincementioning
confidence: 99%